"The red cage": implementation of pH-responsiveness within a macrobicyclic pyridinium-based molecular host. Issue 1 (17th November 2021) - Cortón, Pablo; Wang, Hongye; Neira, Iago; Blanco-Gómez, Arturo; Pazos, Elena; Peinador, Carlos; Li, Hao; García, Marcos D.
Abstract : The "red cage", a new pyridinium-based macrobicyclic host, has been found to complex model aromatic substrates in aqueous media in a pH-responsive fashion. Abstract : We present herein the implementation of pH-responsiveness into a new polycationic macrobicyclic structure, namely what we have termed the "red cage". The hydrolytically-stable cryptand-like compound has been prepared in a relatively high yield in aqueous media by a kinetically-controlled hydrazone-exchange reaction, promoted by the unusual high stability of the new hydrazone CN bonds formed. In organic media the macrobicycle was found not able to complex model aromatic substrates. In buffered aqueous solutions, as a comparison, the "red cage" was found able to recognize them, but the binding was observed to be more efficient in acidic form of the cyclophane compared with its conjugate base.